2006
DOI: 10.1021/jf061471t
|View full text |Cite
|
Sign up to set email alerts
|

Potato Glycoalkaloids and Metabolites:  Roles in the Plant and in the Diet

Abstract: Potatoes, members of the Solanaceae plant family, serve as major, inexpensive low-fat food sources providing energy (starch), high-quality protein, fiber, and vitamins. Potatoes also produce biologically active secondary metabolites, which may have both adverse and beneficial effects in the diet. These include glycoalkaloids, calystegine alkaloids, protease inhibitors, lectins, phenolic compounds, and chlorophyll. Because glycoalkaloids are reported to be involved in host-plant resistance and to have a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
519
2
42

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 545 publications
(572 citation statements)
references
References 270 publications
9
519
2
42
Order By: Relevance
“…This was also confirmed by ESI-MS recorded in positive-ion mode. In fact, the spectrum of AG-2 showed a pseudomolecular ion [M þ H] þ at m/z 414, that is the same observed for leptinidine [20], the common aglycone of leptinines [6], and for the 3-O-b-d-glucopyronoside alkaloid found in wild potato species [21]. In the ESI-MS of AG-3, the pseudomolecular ion [M þ H] þ was observed at m/z 416, which is consistent with an aglycone related to solanidine but probably modified in the perhydropyridine ring.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…This was also confirmed by ESI-MS recorded in positive-ion mode. In fact, the spectrum of AG-2 showed a pseudomolecular ion [M þ H] þ at m/z 414, that is the same observed for leptinidine [20], the common aglycone of leptinines [6], and for the 3-O-b-d-glucopyronoside alkaloid found in wild potato species [21]. In the ESI-MS of AG-3, the pseudomolecular ion [M þ H] þ was observed at m/z 416, which is consistent with an aglycone related to solanidine but probably modified in the perhydropyridine ring.…”
supporting
confidence: 59%
“…By contrast, GAs also have positive effects on plant growth and human diet. As recently outlined by Friedman [6], they may provide protection from damages by insects and fungi, and may have anti-inflammatory and anticancer action.…”
mentioning
confidence: 95%
“…glycoalkaloids (Tga), which are potent poisons [5,[8][9][10]. The lethal dose of these components is 3-5 mg kg −1 body weight, with an effect similar to strychnine or arsenic [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…The potato glycoalkaloids may have evolved in nature to protect the plant against phytopathogens and other hostile environments. 15,16 In our previous studies we had found that several species of Solanum, including the unripe fruits of S. asperum have potentially significant molluscicidal activity. 2,3 The crude alkaloid fraction obtained from the active total MeOH extract as well as the pure alkaloids isolated were tested for the molluscicidal activity (Table 2).…”
Section: Resultsmentioning
confidence: 99%